The Cleridae, Anthribidae and Curculionidae (Coleoptera) described by Ponza - Colonnelli, Enzo; Nardi, Gianluca (Zootaxa, 2019)
An annotated list of the single species of Cleridae and Anthribidae, and two of Curculionidae described by Ponza from the environs of Saluzzo in northwestern Italy, partly overlooked by subsequent authors, is provided. The following new synonymy in Curculionidae is established: Hylobius (Callirus) transversovittatus (Goeze, 1777) [= Curculio brunonianus Ponza, 1805 syn. n.]. The following synonymies are confirmed: Clerus mutillarius mutillarius Fabricius, 1775 [= Attelabus funereus Ponza, 1805] in Cleridae, Dissoleucas niveirostris (Fabricius, 1798) [= Curculio dubius Ponza, 1805] in Anthribidae, and Coniocleonus (Plagiographus) cicatricosus (Hoppe, 1795) [= Curculio spinosus Ponza, 1805] in Curculionidae. Neotypes are not designated, since no long-established name is threatened.